Prevalence, Magnitude and Methods of Rapid Weight Loss Reported by Male Mixed Martial Arts Athletes in Ireland - John Connor; Brendan Egan (MDPI AG, 2019)
Rapid weight loss (RWL) is frequently practiced in weight category sports, including Mixed Martial Arts (MMA). The aim of the present study was to describe self-reported methods of RWL in a sample of competitive MMA athletes comprising of both amateur and professional fighters. The previously-validated Rapid Weight Loss Questionnaire, with the addition of questions on water loading and hot salt baths, was completed anonymously online by athletes (n = 30; all male, n = 15/15 professional/amateur) from MMA clubs around Dublin, Ireland. All but one (97%) of the athletes surveyed lost weight in order to compete, with the average weight loss being 7.9% ± 3.1% of habitual body mass. The RWL score (mean ± SD) for this sample was 37.9 ± 9.6, and a tendency for higher [6.0 (95%CI; −1.1, 13.1) (p = 0.093; d = 0.64)] RWL scores for professional (40.8 ± 8.9) compared to amateur (34.8 ± 9.6) athletes was observed. Frequencies of “always” or “sometimes” were reported as 90% for water loading, 76% for hot salt baths and 55% for 24 h of fasting. Fellow fighters (41%) and coaches/mentors (38%) were “very influential” on RWL practices of these athletes, with doctors (67%), dietitians (41%), and physical trainers (37%) said to be “not influential”. RWL is highly prevalent in MMA across both amateur and professional athletes, and RWL scores are higher than other combat sports. Water loading and hot salt baths are amongst the most commonly used methods of RWL despite little research on these methods for body mass reduction or effects on performance in weight category sports.